2011
DOI: 10.1016/j.ajpath.2010.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Nucleolar Structure and Gene Expression Programs in Prostatic Neoplasia Are Driven by the MYC Oncogene

Abstract: Increased nucleolar size and number are hallmark features of many cancers. In prostate cancer, nucleolar enlargement and increased numbers are some of the earliest morphological changes associated with development of premalignant prostate intraepithelial neoplasia (PIN) lesions and invasive adenocarcinomas. However, the molecular mechanisms that induce nucleolar alterations in PIN and prostate cancer remain largely unknown. We verify that activation of the MYC oncogene, which is overexpressed in most human PIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 48 publications
5
113
1
1
Order By: Relevance
“…Hence, the proto-oncogene responds to nutrient availability, whereas the deregulated oncogene, through gene amplification or chromosomal translocation, for example, severs its ties to the external world, inducing a constitutive growth program that is addicted to nutrients. In this regard, it is notable that MYC expression is elevated in patients with prostate cancer and that MYC plays a central role in murine models of prostate cancer and maintenance of human prostate cancer, such that knockdown of MYC expression results in diminished prostate cancer cell proliferation (5).…”
Section: In the Spotlightmentioning
confidence: 99%
“…Hence, the proto-oncogene responds to nutrient availability, whereas the deregulated oncogene, through gene amplification or chromosomal translocation, for example, severs its ties to the external world, inducing a constitutive growth program that is addicted to nutrients. In this regard, it is notable that MYC expression is elevated in patients with prostate cancer and that MYC plays a central role in murine models of prostate cancer and maintenance of human prostate cancer, such that knockdown of MYC expression results in diminished prostate cancer cell proliferation (5).…”
Section: In the Spotlightmentioning
confidence: 99%
“…14 Increased rDNA expression is associated with chromatin decondensation at the rDNA locus and enlarged nucleoli. 15,16 We therefore checked whether the mutant UBF affects nucleolar architecture. Cells of an affected individual and control were methanol-fixed and subjected to immunofluorescence staining using antibodies recognizing the nucleolar marker nucleolin (Abcam ab50279).…”
mentioning
confidence: 99%
“…More recent studies have shown that this increased size correlates with increased levels of the 45S/5′ETS as well as 5.8S, 18S and 28S rRNA levels (15). Further, prostate cancers have frequent overexpression of MYC which regulates nucleolar size, and common loss of PTEN, which can also activate Pol I transcription and effect nucleolar size and function (2729). …”
Section: Introductionmentioning
confidence: 99%